2003
DOI: 10.1159/000070624
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Therapy in Constitutional Delay of Growth

Abstract: Background/Aims: Two modalities of androgen therapy prevail in the treatment of constitutional delay of growth (CDG): monthly injections of testosterone or daily tablets of the non-aromatizable oxandrolone. The present study was undertaken to prospectively compare both compounds and dose. Methods: Thirty patients with CDG were the subjects of this study. The protocol required that they all be at age 12–14 years with a bone age delay of more than 2 ‘years’, height less than –2 SDS and growth velocity less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
(39 reference statements)
3
11
0
Order By: Relevance
“…Therefore as a consequence, it caused an insignificant change in PAH, similar to that of placebo. These results are in agreement with some reports [6,7], but not with the claims that oxandrolone increases PAH [4,5]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore as a consequence, it caused an insignificant change in PAH, similar to that of placebo. These results are in agreement with some reports [6,7], but not with the claims that oxandrolone increases PAH [4,5]. …”
Section: Discussionsupporting
confidence: 92%
“…The usual treatment is with physiologic doses of androgen, which accelerate linear growth and onset of pubertal changes [1,2,3]. However, they do not improve predicted adult height (PAH) [2,3,4], which is a problem for those with coincidental predicted short stature. Some studies suggest that oxandrolone, an anabolic non-aromatizable androgen, increases PAH [4,5], while others do not [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used clinically to treat boys with constitutional delay of growth and puberty [4] and girls with Turner syndrome [5]. Many studies have confirmed that oxandrolone induces a short-term increase in growth rate in boys with constitutional delay of growth and puberty [6,7,8,9]; an increase that is sustained even after the treatment has been completed [8]. More controversial is the effect of oxandrolone on adult height in these boys.…”
Section: Introductionmentioning
confidence: 99%
“…More controversial is the effect of oxandrolone on adult height in these boys. Some studies show no effect on adult height [8], while others suggest that there might be a positive effect also on adult height in boys who start the treatment before puberty [6, 9]. In girls with Turner syndrome, oxandrolone has been used in combination with growth hormone (GH) therapy and has been shown to increase both growth rate and adult height when given alone or in combination with GH [5].…”
Section: Introductionmentioning
confidence: 99%